Preliminary analysis of lifestyle and genetic factors for hyperuricemia and gout prevalence in the Yunnan Miao population of China - Li, Qiaohong; Khan, Salma Saeed; Yan, Hao; Kong, Weiying; Qin, Lu; Wu, Linmei; Li, Lingjie; Gong, Weijun; Zheng, Hua; Li, Haiyan (Frontiers in Genetics, 2026)
ObjectivesHyperuricemia and gout are common public health problems, stemming from both genetic and lifestyle factors. Evidence from multi-ethnic regions in Yunnan Province remains limited. This preliminary study examined hyperuricemia and gout prevalence, related biomarkers, lifestyle patterns, and SLC2A9/SLC22A12 genetics variations among 88 participants from the Miao community in Yunnan Province China.MethodsA cross-sectional survey and biochemical study were conducted. Demographic and lifestyle data were collected, and blood samples were analyzed for serum biochemical indicators. Eight SNPs in SLC2A9 and SLC22A12 were genotyped. Logistic regression models were applied to allele and genotype data.ResultsDemographic and clinical analyses for Miao villagers (n = 88) suggested that the morbidities of hyperuricemia and gout were more frequent in male and showed significant association with alcohol consumption, smoking, and elevated BMI. While dietary patterns showed no significant differences. Compared with non-hyperuricemia/non-gout individuals (n = 56), the hyperuricemia/gout group (n = 57) showed 56% higher uric acid (553.13 vs. 354.73 μmol/L), 37% elevated creatinine (84.66 vs. 61.80 μmol/L), and higher triglycerides (3.35 vs. 1.80 mmol/L), along with hematological abnormalities, e.g., elevated hemoglobin (162.77 vs. 147.50 g/L) and lower platelets counts (161.09 vs. 194.14 × 109/L). Preliminary genetic analyses indicated a possible association between SLC2A9_rs10939650 and hyperuricemia/gout risk, whereas variant SLC22A12 polymorphisms showed no association. After Bonferroni correction, no SNPs remained statistically significant.ConclusionThis preliminary study suggested that the relatively higher burden of hyperuricemia and gout in the Miao population may be influenced by ethnicity, sex, lifestyle factors, metabolic alteration, and potential genetic components. Given the small sample size, the genetic findings should be interpreted cautiously and validated in larger studies for that disease (hyperuricemia and gout) and for similar ethnic community.